Rab-SPIRE interaction: the molecular mechanism of the interaction between Rab27a and SPIRE1 - Alghamdi, Asmahan (2023)
Rab27a is a small GTPase that regulates organelle transport and exocytosis by recruiting effector proteins to membranes. SPIRE1/2 are membrane associated actin nucleators recently identified as Rab27a effectors. In melanocytes they interact with Rab27a via their C-terminal domains (SFH) and assemble actin filaments (AFs) required for melanosome transport. To better understand their interaction, this thesis aimed to obtain a homogenous 1:1 protein population that is a prerequisite for X-ray crystallography. This was done by following a dual-expression approach that depends on using the same vector to express the two proteins in the same cells where they can form a complex, then purifying the complex utilizing affinity chromatography methods. The obtained results indicate Rab27 intactness, unlike SFH, that is obviously instable/truncated. Several attempts were made to tackle this problem, albeit with little positive impact. To overcome SPIRE instability/truncation, synthetic SPIRE peptide was used for binding studies with purified Rab27a followed by affinity chromatography. The binding and co-purification results indicate a specific peptide-Rab27 binding and that some of the complex is purified. However, further optimisations to maximize the amount of the Rab27 in the purified complex are required. Therefore, to enable the interaction to be characterised, a 1:1 complex of Rab27a:SPIRE1 SFH was modelled using AlphaFold2-Multimer. This indicates that Rab27a adopts a globular fold typical of small GTPases. Like the Rab27 interface of other effectors, SFH structure consists of an elongated helical fold and a Zn+2 binding domain. The model suggests that the N-terminal helix which has high similarity to the Rab-interface of other Rab27/3 effectors is the main Rab27a interface in SPIRE1 contacting the Rab switch and interswitch regions. This is consistent with the outcomes of preliminary investigations of the binding of SPIRE fragments lacking this element to Rab27a. Studies testing the role of predicted Rab27a contact residues in SPIRE1 in a melanocyte-based interaction assay support the predictions of the model and further support the hypothesis that SPIRE interacts with Rab27 similarly to other effectors. Overall, this work supports the idea that parallel in-silico modelling of protein structure and experimental testing offers a rapid approach to investigate protein-protein interactions where structures are not available.